T4SS-dependent TLR5 activation by Helicobacter pylori infection - Suneesh Kumar, Pachathundikandi; Tegtmeyer, Nicole; Arnold, Isabelle Catherine; Lind, Judith; Neddermann, Matthias; Falkeis-Veits, Christina; Chattopadhyay, Sujay; Brönstrup, Mark; Tegge, Werner; Hong, Minsun; Sticht, Heinrich; Müller, Anne; et al. (Nature Communications, 2019)
Toll-like receptor TLR5 recognizes a conserved domain, termed D1, that is present in flagellins of several pathogenic bacteria but not in Helicobacter pylori. Highly virulent H. pylori strains possess a type IV secretion system (T4SS) for delivery of virulence factors into gastric epithelial cells. Here, we show that one of the H. pylori T4SS components, protein CagL, can act as a flagellin-independent TLR5 activator. CagL contains a D1-like motif that mediates adherence to TLR5+ epithelial cells, TLR5 activation, and downstream signaling in vitro. TLR5 expression is associated with H. pylori infection and gastric lesions in human biopsies. Using Tlr5-knockout and wild-type mice, we show that TLR5 is important for efficient control of H. pylori infection. Our results indicate that CagL, by activating TLR5, may modulate immune responses to H. pylori.
CRIS-Team Scopus Importer:2019-12-27